MEZO INSTITUTIONS IN SPACE OF SOCIO-ECONOMIC LIFE - Pizło, Wojciech (Acta Scientiarum Polonorum. Oeconomia, 2008)
The article presents results of theoretical research, which apply to organizations in institutional theory. It was presented characteristic of institution in the point of view in human sciences (prakseology, sociology, anthropology and economics) and division of the institutions described by Szczepański, based on the institutional human needs as well as four level horizontal socio-economic analyze (model by Williamson). This article was discussing the role of institution in mezo space (organizations space) and describing three forms of organizations: community, association and corporation.